2019
DOI: 10.3389/fpsyt.2019.00418
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Interhemispheric Functional Connectivity in Obsessive–Compulsive Disorder Patients

Abstract: Background: Neuroimaging studies have shown that the high synchrony of spontaneous neural activity in the homotopic regions between hemispheres is an important functional structural feature of normal human brains, and this feature is abnormal in the patients with various mental disorders. However, little is known about this feature in obsessive–compulsive disorder (OCD). This study aimed to further analyze the underlying neural mechanisms of OCD and to explore whether clinical characteristics are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 58 publications
3
20
0
Order By: Relevance
“…Decreased VMHC outside the CSTC circuits, such as the middle occipital, precentral, and postcentral gyri, in patients with OCD at rest in our study is similar to the results of Deng et al. ( 21 ). The occipital cortex is involved in the pathophysiology of OCD because of its connection with the CSTC circuits ( 4 , 36 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Decreased VMHC outside the CSTC circuits, such as the middle occipital, precentral, and postcentral gyri, in patients with OCD at rest in our study is similar to the results of Deng et al. ( 21 ). The occipital cortex is involved in the pathophysiology of OCD because of its connection with the CSTC circuits ( 4 , 36 ).…”
Section: Discussionsupporting
confidence: 92%
“…A recent meta-analysis discovered that patients with OCD showed hypoactivation in the bilateral thalamus and medial OFC during inhibitory control ( 35 ). Decreased VMHC values in the OFC and thalamus in patients with OCD at rest were also observed in other studies ( 21 , 22 ). The present and previous studies supported the disconnection between homotopic brain regions within the CSTC circuits in patients with OCD, which might lead to obstacles in the communication and integration of cognitive and emotional information in OCD ( 15 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The authors' research and other studies previously found decreased FC within the CSTC circuits at rest in OCD (Wang et al, 2018;Deng et al, 2019;Jia et al, 2020). Although these researchers found that FC strength seemed to exhibit functional asymmetry, they did not explore functional asymmetry of the interhemispheric and/or intra-hemispheric FC at rest in OCD.…”
Section: Discussionmentioning
confidence: 78%
“…Apart from structural abnormalities, functional studies also highlight the importance of trans‐callosal connectivity alterations in OCD. Adult patients with OCD have been reported to have decreased functional connectivity between the right ventral lateral prefrontal cortex and left insula (Chen et al., 2018) and decreased voxel‐mirrored homotopic connectivity in the precentral gyrus and orbitofrontal cortex (Deng et al., 2019). Additionally, increased functional frontal asymmetry in patients with OCD has been observed in electroencephalography studies (Perera et al., 2019).…”
Section: Discussionmentioning
confidence: 99%